Digital monetary system and social relations: legal realities and prospects of the implementation mechanism - Kharytonov, Evgen; Kostruba, Anatoliy; Davydova, Iryna (Journal of the University of Zulia, 2022)
This text offers a reflection on the legal aspects of the implementation of the digital money system in Ukraine and abroad. The authors also analyzed and modeled the directions of development of social relations arising from the use of digital money in various spheres of people’s lives. In particular, the authors of the study identify the details of the impact of the digital monetary system in ensuring stability and the implementation of monetary policy in the financial sphere. Likewise, the potential impact of the use of digital money in the banking system is analyzed. The authors investigated the possibility of ensuring the transparency of transactions and control over the circulation of digital money, and proposed the appropriate legal mechanisms that must be implemented for the effective functioning of the digital money system.